Applications in basic marketing. - McCarthy, E. Jerome (Edmund Jerome); Perreault, William D.; McCarthy, E. Jerome (Edmund Jerome); McCarthy, E. Jerome (Edmund Jerome) (Irwin, 2005)
"Clippings from the popular business press."